2013
DOI: 10.1542/peds.2013-0470
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Characteristics of Dying Children Who Receive and Do Not Receive Palliative Care

Abstract: OBJECTIVE: Comparing demographic and clinical characteristics associated with receipt of palliative care (PC) among children who died in children’s hospitals to those who did not receive PC and understanding the trends in PC use. METHODS: This retrospective cohort study used the Pediatric Health Information System database. Children <18 years of age who died ≥5 days after admission to a Pediatric Health Information Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(151 citation statements)
references
References 20 publications
6
139
1
4
Order By: Relevance
“…We excluded a further 3656 after screening the titles and abstracts, and retrieved 109 papers for full-text review (κ value = 0.25, 95% confidence interval [CI] 0.22-0.28, indicating fair agreement according to Fleiss 9 ). Nine articles fulfilled the inclusion criteria (Figure 1), 5,[10][11][12][13][14][15][16][17] (κ = 0.83, 95% CI 0.64-1.00, indicating almost perfect agreement). Two additional studies 18,19 were identified in the weekly automated search updates, for a total of 11 included studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…We excluded a further 3656 after screening the titles and abstracts, and retrieved 109 papers for full-text review (κ value = 0.25, 95% confidence interval [CI] 0.22-0.28, indicating fair agreement according to Fleiss 9 ). Nine articles fulfilled the inclusion criteria (Figure 1), 5,[10][11][12][13][14][15][16][17] (κ = 0.83, 95% CI 0.64-1.00, indicating almost perfect agreement). Two additional studies 18,19 were identified in the weekly automated search updates, for a total of 11 included studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Four cohort comparisons 11,12,14,15 used administrative data and survey techniques 14 to explore differences between cohorts of children with and without access to PPCPs. Observation periods varied, from the last day of admission before death to the referral to a PPCP.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past 5 years, .130 peerreviewed publications have used this database to study national inpatient pediatric care delivery. [16][17][18][19][20][21] We chose not to use the KID for analysis of patterns in freestanding children' s hospitals because it has a 9% missing rate for hospital type.…”
Section: Data Sourcesmentioning
confidence: 99%